A history of Modern Palestine - Pappé, Ilan (Cambridge University Press, 2022)
"On the eve of the Crimean War, about half a million people lived in the land of Palestine. They were Arabic-speaking. Most were Muslims, but about 60,000 were Christians of various denominations, and around 20,000 were Jews. In addition, they had to tolerate the presence of 50,000 Ottoman soldiers and officials as well as 10,000 Europeans. Their administrative life revolved around the sanjaq, the Ottoman sub-province, of which Ottoman Palestine had three: Nablus, Acre and Jerusalem. To some extent these administrative divisions corresponded to the topography. Palestine had four hilly regions: the Jerusalem mountains, the Nablus mountains, and two other areas: Hebron in the Jerusalem district, and Galilee in the Acre sub-province. Each geographical and administrative area had a major town as its capital, so that some of Palestine's most famous cities were foci of social and cultural life. Acre, Jerusalem, Hebron and Nablus were among these important towns, as were the smaller coastal towns of Haifa, Jaffa and Gaza"--